Upaya Pemerintah Kabupaten Dairi Sumatera Utara dalam Meningkatkan Kepatuhan Wajib Pajak Kendaraan Bermotor - Ayu Agrostin Sipangkar; Nurmayani Nurmayani; Marlia Eka Putri AT (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Motor Vehicle Tax (PKB) is one of the strategic sources of Regional Own-Source Revenue (PAD) for Dairi Regency, North Sumatra Province. PKB, as a provincial tax, is regulated under Law Number 1 of 2022, and its implementation in North Sumatra Province is governed by North Sumatra Provincial Regulation Number 1 of 2024. However, the level of PKB taxpayer compliance in this region still faces various challenges, as reflected in the decline of PKB Revenue-Sharing Fund receipts by 48.77%, from IDR 7.76 billion in 2023 to IDR 3.97 billion in 2024. This study aims to examine: 1) the level of motor vehicle taxpayer compliance in Dairi Regency, and 2) the efforts made by the Dairi Regency government to improve such compliance. This study employs an empirical juridical research approach, conducted through primary data collection via interviews with the UPTD Samsat Sidikalang office and the distribution of online questionnaires to 40 PKB taxpayers. Data analysis was carried out using a descriptive qualitative method. The findings indicate that PKB taxpayer compliance in Dairi Regency remains formal and reactive in nature, and has yet to reflect substantive compliance arising from a deep legal awareness. A number of taxpayers still delay payment until a tax amnesty program is announced. In efforts to improve compliance, the Dairi Regency government has implemented various programs, including: mobile Samsat units, Samsat outlets, E-Samsat, tax socialization and education through social media, the Mandiri Ketuk Pintu Program (PMKP), joint vehicle inspection operations, and tax amnesty policies. All of these efforts represent the implementation of the mandate set forth in Law Number 1 of 2022 on Fiscal Relations between the Central Government and Regional Governments, aimed at optimizing PAD in order to support sustainable regional development.